Cross-sectional associations between inflammation, sickness behaviour, health anxiety and self-rated health in a Swedish primary care population. (April 2019) - Lodin, Karin; Lekander, Mats; Petrovic, Predrag; Nilsonne, Gustav; Hedman-Lagerlöf, Erik; Andreasson, Anna
This study investigated associations between inflammatory markers, sickness behaviour, health anxiety and self-rated health in 311 consecutive primary care patients. Poor self-rated health was associated with high sickness behaviour ( ρ = 0.28, P < 0.001; ρ = 0.42, P = 0.003) and high health anxiety ( ρ = 0.31, P < 0.001; ρ = –0.32, P = 0.003). High levels of interleukin 6 were associated with poor self-rated health in men ( ρ = 0.26, P = 0.009). Low levels of interleukin-6 were associated with poor self-rated health in women ( ρ = –0.15, P = 0.04), but this association was non-significant when adjusted for health anxiety ( ρ = –0.08, P = 0.31). These results are consistent with the theory that interoceptive processes draw on both inflammatory mediators and the state of sickness behaviour in inferring health state.